Real-world impact of latanoprostene bunod ophthalmic solution 0.024% in glaucoma therapy: a narrative review - Stamer, W. Daniel; Chiu, Thomas; Lu, Da-Wen; Wang, Tsing Hong; Rojanapongpun, Prin; Ruangvaravate, Ngamkae; Jo, Youn Hye; Moster, Marlene R.; Fingeret, Murray; Cothran, Nora Lee; Steen, Jessica; Gaddie, Ian Benjamin; et al. (Frontiers in Ophthalmology, 2025)
Latanoprostene bunod ophthalmic solution (LBN) 0.024% is a topical nitric oxide (NO)-donating prostaglandin F2α (PGF2α) analog first approved in November 2017 for reduction of intraocular pressure (IOP) in patients with ocular hypertension (OHT) or open-angle glaucoma (OAG). This narrative review describes the unique mechanism of action of LBN and summarizes available real-world data. Upon instillation, LBN is metabolized into latanoprost acid and butanediol mononitrate, which is further reduced to NO and an inactive metabolite. Latanoprost acid increases aqueous humor outflow primarily through the uveoscleral (unconventional) pathway, whereas NO increases outflow through the trabecular (conventional) pathway. Eight studies were identified: 2 studies in newly diagnosed, treatment-naïve patients with OHT or OAG, 4 studies of adjunctive therapy in patients with glaucoma receiving other IOP-lowering therapies, and 2 studies in which patients with glaucoma switched to LBN monotherapy or adjunctive therapy. Decreases in IOP after initiating LBN in newly diagnosed patients or adding/switching to LBN were generally consistent with reductions observed in clinical trials and sustained throughout the studies. Rates of discontinuation due to inadequate IOP lowering ranged from 12.2% to 17.1%. LBN was generally well tolerated in real-world studies; the most common adverse events were consistent with the known safety profile of LBN. Data from real-world studies provide important insights regarding the potential effectiveness and tolerability of LBN in the clinical setting and suggest that LBN is well tolerated and associated with significant, clinically meaningful, and durable reductions in IOP.